1993
DOI: 10.1007/bf01309548
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity in the surface-exposed amino-terminal region of the coat proteins of seven strains of sugarcane mosaic virus correlates with their host range

Abstract: The N-terminal region of the coat proteins of five strains (Isis, Brisbane, Sabi, Bundaberg, and BC) of sugarcane mosaic virus (SCMV) isolated from four different plant species (sugarcane, sabi grass, wild sorghum, and blue couch grass) have been compared with the previously published data for SCMV-SC and SCMV-MDB, isolated from sugarcane and maize, respectively. The region, beginning at residue 11 and ending 16 residues beyond the second trypsin cleavage site of the coat protein, varied in size from 68 amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 16 publications
2
23
0
1
Order By: Relevance
“…Our results confirm that between isolates of PRSV, the core is also conserved and the N terminus is most variable. Xiao et al (1993) suggested that the N terminus may be involved in host specificity. However, we have found no obvious sequence changes, either nucleotide or amino acid, that would account for the difference between PRSV-P and PRSV-W. Interestingly, the C terminus of the coat protein was highly conserved between all PRSV isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm that between isolates of PRSV, the core is also conserved and the N terminus is most variable. Xiao et al (1993) suggested that the N terminus may be involved in host specificity. However, we have found no obvious sequence changes, either nucleotide or amino acid, that would account for the difference between PRSV-P and PRSV-W. Interestingly, the C terminus of the coat protein was highly conserved between all PRSV isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Sugarcane mosaic virus (SCMV) causes severe dwarf mosaic disease in maize (Zea mays), sugarcane (Saccharum sinensis), and sorghum (Sorghum vulgare; Xiao et al, 1993). It is known as a major viral pathogen of maize in China, and the Beijing isolate (SCMV-BJ) belongs to a prevalent strain of SCMV in China (Fan et al, 2003).…”
mentioning
confidence: 99%
“…The N-terminal coat protein region of AbaMV had amino acid repeats (Fig. 3) which differed from those published for other SCMV isolates, including SCMV-MDB, SCMV-SC and SCMV-Sabi (Xiao et al 1993;Ward et al 1995). There were no amino acid repeats detected in BBrMV that were similar to those in AbaMV.…”
Section: Sequence Analysesmentioning
confidence: 73%
“…It has been suggested that host specificity and virulence are determined by the coat protein, especially the N-terminal region, which varies in size and similarity between the SCMV subgroup members (Xiao et al 1993). However, the N-terminal repeat sequences described for the maize-infecting SCMV-MDB (Xiao et al 1993) are not present in maize-infecting isolates of SCMV from Germany (Oertel et al 1997).…”
Section: Discussionmentioning
confidence: 99%